Avaliação da angulação das coroas dentárias em más oclusões de classe III por meio de modelos digitais - Dias, Josenira Borges (2015)
Class III maloclusions present characteristic to skeletal involvement: maxillary deficiency and / or mandibular prognathism are present, manifesting slow and progressive manner over growth, requiring and allowing adjustments in tooth positions to maintain occlusal relationships for exercise function. This phenomenon called "compensation" occurs more frequently in class III malocclusion and should be kept in its essence whenever orthodontic treatment is indicated. Described in a limited way in the literature, restricting to the inclination of incisors in most of the investigations, it seemed consistent investigate the angulation of dental crowns using digitized models of dental arches of a sample of patients with malocclusion Class III who need compensatory orthodontic treatment. They were selected 46 plaster models of individuals of both sexes (25 men and 21 women) with a mean age of 21 anos e 1 mês, maximum 44 years and three months and a minimum of 11 years and 9 months, people with Class III malocclusions, white, orthodontic treatment indication, absence of tooth loss and permanent dentition. These models were scanned and the measurement of the angle of dental crowns was performed by the Abzil BI program. The results were compared with normal values considered for white Brazilians with normal occlusion available literature. The angulation of dental crowns in Class III malocclusions, compared with the normal showed upper anterior teeth with positive angles, smaller and with no significant differences and upper posterior teeth with decreased angle, with statistical significance. In the lower arch anterior teeth exhibited negative angles, with no significant differences and the posterior teeth showed smaller angles and significant for canines and first pre molar, while the remaining teeth showed higher angles, with statistical significance for first and second molars .In this context, it was concluded that the natural compensation was present, just for canines and first premolars